Parental Support and Involvement to Children in Learning English as a Foreign Language - Nauvianti, Umdatussy (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2025)
Successful use of English with children depends on support from the wider environment. Children learn English in two settings: at home and at school. However, solely implementing English in a school setting can be challenging. Time constraints and inadequate teaching materials hinder the process. Parents must provide support and involvement in their children's English language acquisition to enhance its use as a companion language. This study outlines the factors that parents should consider when supporting and involving their children in the development of English as a companion language for communication, both at home and in a social environment. Furthermore, it focuses on the value of parents taking a systematic approach to establishing a supportive and advancing English language learning environment in the household. By having descriptive qualitative as its research design, the study included 5 participants, parents aged 25 to 50 with children aged 5 to 12. They consistently support and engage in their children's internal and external English language learning activities. The researcher conducted interviews to collect data. Prior to commencing the interviews, the researcher formulated a series of questions addressing the topics of discussion and documented their observations through writing and/or recording the interviews. The result shows how parents can motivate and participate in their children's improvement in English. These include providing intellectual, emotional, and financial support and involvement. This study is part of a growing body of research on parental support toward children’s language development. The project is going to contribute to future research on similar field.